The fatburn fix : boost energy, end hunger, and lose weight by using body fat for fuel - Shanahan, Catherine (Flatiron Books, 2020)
"A proven plan to optimize your health by reclaiming your natural ability to burn body fat for fuel. The ability to use body fat for energy is essential to health-but over decades of practice, renowned family physician Catherine Shanahan, M.D., observed that many of her patients could not burn their body fat between meals, trapping them in a downward spiral of hunger, fatigue, and weight gain. In The Fatburn Fix, Dr. Shanahan shows us how industrially produced vegetable oils accumulate in our body fat and disrupt our body's energy-producing systems, driving food addictions that hijack our moods and habits while making it nearly impossible to control our weight. To reclaim our health, we need to detoxify our body fat and help repair our "FatBurn" capabilities. Dr. Shanahan shares five important rules to fix your FatBurn: 1) Eat natural fats, not vegetable oils. 2) Eat slow-digesting carbs, not starchy carbs or sweets. 3) Seek salt. 4) Drink plenty of water. 5) Supplement with vitamins and minerals. She then provides a revolutionary, step-by-step plan to help reboot your FatBurn potential in as little as two weeks. This customizable two-phase plan is widely accessible, easy to follow, and will appeal to the full spectrum of diet ideologies, from plant-based to carnivore to keto and beyond. By making a few changes to what you eat and when, you will lose unwanted weight and restore your body's ability to store and release energy. With The Fatburn Fix, Dr. Shanahan shows how regaining your FatBurn is the key to effortless weight loss and a new, elevated life, paving the way to abundant energy and long-term health and happiness"--